2014
DOI: 10.5455/2320-1770.ijrcog20140332
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of congenital malformations and their possible risk factors in a teaching hospital in Punjab

Abstract: Background: Congenital malformations (CMF) are third most common cause of perinatal mortality in India making their prediction and prevention highly eminent. The present study was designed to analyze the frequency, distribution and patterns of CMF among babies born in a teaching hospital in Punjab, along-with factors contributing towards their occurrence. Methods: This was a prospective study in which the incidence of CMF was determined in 1554 consecutive deliveries conducted at Gian Sagar Medical College, Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 10 publications
1
19
1
Order By: Relevance
“…1,8,9,12,15 Babies with history of consanguinity had higher incidence of malformations as compared to those with no such history but the difference was not statistically significant which is similar to the findings of Patel et al, Sarkar et al, Marwah et al and Taksande et al while Parmar et al found no association of consanguinity with congenital malformations. 1,9,11,15,18 Our study had limitations of being an exclusive hospital based study accounting for mostly referred patients. Larger population based studies are required to determine the actual prevalence of these disorders in the population.…”
Section: Fetal Factorssupporting
confidence: 80%
See 3 more Smart Citations
“…1,8,9,12,15 Babies with history of consanguinity had higher incidence of malformations as compared to those with no such history but the difference was not statistically significant which is similar to the findings of Patel et al, Sarkar et al, Marwah et al and Taksande et al while Parmar et al found no association of consanguinity with congenital malformations. 1,9,11,15,18 Our study had limitations of being an exclusive hospital based study accounting for mostly referred patients. Larger population based studies are required to determine the actual prevalence of these disorders in the population.…”
Section: Fetal Factorssupporting
confidence: 80%
“…Most common system involved in our study was central nervous system (48%) followed by musculoskeletal (28%) and gastrointestinal (13%) which is similar to the observations of other studies. 1,8,10,12,15,16 However, Sarkar et al reported that musculoskeletal anomalies were the commonest. 9 Cardiac anomalies were reported to be most common by some studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indian studies showed similar results. [21][22][23] The etiology of CNS malformations is multifactorial, involving complex interactions between genetic and environmental factors, constituting one of the most common congenital defects. 22,24,25 Sunitha et al 22 analyzed 360 pregnant women with fetuses presenting structural abnormalities, and also observed a higher frequency of CNS anomalies (37%), followed by genitourinary system abnormalities (20%) and multiple CAs (11%).…”
Section: Discussionmentioning
confidence: 99%